Analysis of product design in developing learning aids for dyslexic children / Siti Nur Solehah ... [et al.] - Solehah, Siti Nur; Faaizah, Wan Noor; Azizan, Hasnul Azwan (Universiti Teknologi MARA, Kedah, 2022)
This paper explores areas of product design in designing the learning aids for dyslexic children that rely on data definition. All of the data gathered were evaluated using suitable approaches, such as quantitative methods. The data were analysed using Statistical Package for Social Sciences or known as SPSS software. The bar graphs are shown using Microsoft Excel. In this study, the data were gained from a focus group comprising the educator and the parents of dyslexic student. All data were gathered to uncover a viable solution to the problem. This paper shows the analysed data to develop product learning aids from five designs that were developed from the collected data and existing product.